STRENGTHENING AWARENESS OF PAYING ZAKAT - MA, Roikhan; Muttaqin, Zainal; Ari, Dita NA (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2021)
This study aims to analyze the interdependence of several variables simultaneously to form a relationship among several variables studied into several factors to pay zakat. This study was conducted by primary data and also from literature work such as journal, book and internet media. The data based on 100 respondents from government institutions, the Office of the Mayor of West Jakarta and Centre Jakarta. Methodology uses quantitative approach with factor analysis tool. The results of this study indicates the variables studied were formed into five factors, such as the work factor, the value orientation factor, the education factor, the subjective norm factor, and the zakat factor. The total variance of the five factors are two thirds that these five factors can help zakat payers awareness in paying zakat, while the remaining one third are supported by other factors outside of the five factors.